2017
DOI: 10.1186/s12936-017-1685-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of mosquito egg production under mass rearing setting: effects of cage volume, blood meal source and adult population density for the malaria vector, Anopheles arabiensis

Abstract: Background Anopheles arabiensis is one of the major malaria vectors that put millions of people in endemic countries at risk. Mass-rearing of this mosquito is crucial for strategies that use sterile insect technique to suppress vector populations. The sterile insect technique (SIT) package for this mosquito species is being developed by the Insect Pest Control Subprogramme of the Joint FAO/IAEA Division of Nuclear Techniques in Food and Agriculture. To improve mass-rearing outcomes for An. arabiensis, the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
22
0
2
Order By: Relevance
“…Artificial blood-feeding systems should be developed in any mosquito mass rearing facility. The uses of natural and artificial membranes, such as collagen sausage skins, bovine intestines (cleaned) and Parafilm, have been tested for several mosquito species [ 10 , 18 , 19 , 30 – 32 ]. The blood temperature is an important parameter for feeding responses of females [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial blood-feeding systems should be developed in any mosquito mass rearing facility. The uses of natural and artificial membranes, such as collagen sausage skins, bovine intestines (cleaned) and Parafilm, have been tested for several mosquito species [ 10 , 18 , 19 , 30 – 32 ]. The blood temperature is an important parameter for feeding responses of females [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prototype of a mass production cage (MPC), based on the cage design used for Medflies in Guatemala, which has been modified to allow blood-feeding, sugar-feeding and oviposition for simplified collection of the eggs, has been tested for both Ae. albopictus [ 18 ] and Anopheles arabiensis [ 19 ]. The MPC cage was designed to reduce handling and the opening of the cages during operation such as for blood-feeding and egg collection, but the egg production of Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result showed that a maximum egg production could be achieved in the mass rearing unit from females from all treatments. Indeed, the largest number of eggs has been found to be produced within the mass rearing cage during the first 15 days [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…De forma geral, aproximadamente 10 % do total de ovos produzidos em uma criação em massa são usados para a manutenção da própria colônia matriz e o restante, para a produção de lotes dos machos para liberação (CARVALHO et al, 2014;ZHANG et al, 2018) (ZHANG et al, 2018). Entretanto, devem ser tão ou mais eficientes que as gaiolas pequenas (PVC), sem reduzir a fecundidade e a taxa de eclosão dos ovos (BALESTRINO et al, 2014;MAMAI et al, 2017;ZHANG et al, 2018). Portanto, quando eficientes, são estratégicas para o aprimoramento de uma criação em massa e contribuem para a redução dos custos operacionais.…”
Section: Meta I-plano De Aplicação Em Massa Da Linhagem Mbr-001unclassified